Os caminhos da inclusão social à luz da Política Nacional de Resíduos Sólidos: um olhar sobre a categoria dos catadores de materiais reutilizáveis e recicláveis - Silveira, Raquel Maria da Costa (2019)
In August 2010, the National Solid Waste Policy - (Federal Law No. 12,305) went into force in Brazil. Through the validity of such law, municipal responsibilities were proposed regarding the integrated management of solid waste. It was indicated that recyclable and reusable material collectors should be part of the municipal selective waste collection programs. The law also specified that it is necessary to promote economic emancipation and social inclusion of these historically excluded individuals. As a model for social inclusion, the policy clarifies information regarding the need to create of self-managed organizations (cooperatives and associations) of collectors as well as the need to hire them for municipal selective collection. Although, in Brazil, these types of contracts are not yet common, these organizations are being included in the selective collection programs. On the other hand, the existence of different internal realities within these organizations may lead to the need of further research related to local public support that may in the long run, avert the organizations away from the legally established goals. Thus, the following research questions were proposed: In the same realm of relations, do organization, collectors and the municipal public power have the same capacity of social inclusion? What factors contribute to distancing organizations from the reach the legal purposes? It is assumed that the relationship between collectors, municipal public power issues such as the effectiveness of the municipal selective collection program, the diversity of partnerships established by the organizations, the leadership on behalf of representatives and the self-management capacity of the organizations contribute to the existence of different inclusion realities. Thus, this work aims to study the social inclusion of Recyclable Materials Collectors according to the established model within the Brazilian National Solid Waste Policy. In order to carry out the study, it was essential to discuss the labor activity carried out by these collectors and present the Brazilian model of social inclusion of these individuals according to national Law 12,305 guidelines. After this research phase, case studies were carried out. These considered the recyclable materials collectors organizations in Rio de Janeiro Curitiba and Natal. In order to address the specific realities of the selected organizations, the sustainability indicators developed by the Brazilian National Health Foundation in 2017 were used as guidelines. It was possible to analyze leadership profiles of those who were responsible for the organization during the research. In the end, it was verified that organizations that have the same support offered by the public power presented a differentiated capacity according to aspects such as the president leadership profile, effectiveness of the municipal selective collection program, as well as the diversity of partnerships organizations. In addition to this, and in spite of legal predictions, the surveyed organizations still presented challenges related to management, operational efficiency, working conditions, health and safety on behalf of the collectors.